Digital competencies for TVET educators: a framework for professional development - Liu, Jun Qiong; Muhammad Khair Noordin; Muhammad Afandi Azmi; Ahmad Nabil Md Nasir; Mahyuddin Arsat (Penerbit Universiti Kebangsaan Malaysia, 2024)
Digitization in the field of Technical and Vocational Education and Training (TVET) has now become an integral part of our world today. This means that instructors in this field should be well equipped with digital skills if they are to offer their learners an effective instruction within a digital environment. This article puts forward a framework for nurturing digital competences among TVET instructors and shares findings of an empirical study. The framework is made up of five main components for digital teaching. In order to achieve this objective, a research was done where a survey was conducted on various MTUN universities. The results showed that majority did not have enough knowledge in using technology to teach effectively. The study also brought out some challenges faced when trying to implement such training programs on how to raise these competencies within TVET systems which were lack of resources, limited time and reluctance among staff members themselves. This research can be of great help to TVET institutions and governments who want to improve the digital capabilities of their instructors in the TVET sector. These findings may be used as a guide in training programs development for instructors teaching TVET subjects. Eventually it will contribute towards understanding how important digital competence is within TVET while at the same time underlining its role as being an essential skill needed to meet the demands of contemporary society characterized by increasing use of technology in all spheres of life.